Migration taxes and human capital formation: Some implications for development - Saibal Kar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Use of migration tax as an instrument for financing development expenditure in poorer countries has received renewed attention recently and is evolving as an important subject of research in development economics. This paper discusses a related issue where the revenue collected by taxing skilled and unskilled migrants moving from poor to rich countries can help raising the level of human capital in the source country. The paper provides an unifying analysis for two distinct strands of literature-one claims that lack of restriction on skill migration promotes human capital formation and the other, the more conventional one, argues for greater restriction against negative impact of brain drain. Considering that both human capital formation and migration involve risk, we then explore a connection between imposition of migration tax, human capital formation and risk aversion. For a country with low level of human capital to start with, we establish that a proportionally higher migration tax imposed on the unskilled migrants considerably raises the average level of human capital for all nonmigrants. The disincentive effect of the migration tax and its use as educational subsidy shifts the critical relative risk aversion among the non-migrants in favour of acquiring more human capital. The proposed migration tax pattern also raises the average income level of all individuals and only conditionally for the non-migrants.
Keywords: H24; J24; J31; J61; 330; migration tax; human capital; skill; risk aversion; Entwicklungsfinanzierung; Internationale Wanderung; Humankapital; Personalsteuer; Theorie; Entwicklungsländer